Mortality in Innu communities in Labrador, 1993-2018: a cross-sectional study of causes and location of death - Russell Dawe; Jack Penashue; John C. Knight; Andrea Pike; Mary Pia Benuen; Anastasia Qupee; Nathaniel J. Pollock (International Journal of Circumpolar Health)
In Canada, most people prefer to die at home. However, the proportion of deaths that occur in hospital has increased over time. This study examined mortality rates and proportionate mortality in Innu communities in Labrador, and compared patterns to other communities in Labrador and Newfoundland. We conducted a cross-sectional ecological study with mortality data from the vital statistics system. This included information about all deaths in Newfoundland and Labrador from 1993 to 2018. We used descriptive statistics and rates to examine patterns by age, sex, cause and location. During the 2003 to 2018 period the leading cause of death in the Innu communities (excluding external causes) was cancer, followed by circulatory disease and respiratory disease. Between 1993 and 2018, there was a lower percentage of hospital deaths and a higher percentage of at home deaths in Innu communities than in the rest of the province. The majority of deaths among Innu were due to cancer and chronic diseases. We found a higher percentage of at home deaths in Innu communities compared to the rest of the province.